A new Europe, 1918-1923
1 online resource (272 pages).
Keywords: This set of essays introduces readers to new historical research on the creation of the new order in East-Central Europe in the period immediately following 1918. The book offers insights into the political, diplomatic, military, economic and cultural conditions out of which the New Europe was born. Experts from various countries take into account three perspectives. They give equal attention to both the Western and Eastern fronts; they recognise that on 11 November 1918, the War ended only on the Western front and violence continued in multiple forms over the next five years; and they show how state-building after 1918 in Central and Eastern Europe was marked by a mixture of innovation and instability. Thus, the volume focuses on three kinds of narratives: those related to conflicts and violence, those related to the recasting of civil life in new structures and institutions, and those related to remembrance and representations of these years in the public sphere. Taking a step towards writing a fully European history of the Great War and its aftermath, the volume offers an original approach to this decisive period in 20th century European history.